Infantile malignant osteopetrosis (Leontiasis ossea) in a mid-19th c. French skull. (March 2020) - Benmoussa, Nadia; Muller, Anne-Laure; Fanous, Amanda; Deo, Saudamini; Conan, P.; Charlier, P.
Highlights: Study of a 19th century skull confirms that this patient suffer of malignant osteopetrosis. Skeletons from medical anatomical museums allow us to understand the first case of rare disease. CT-scan permitted to confirm diagnosis and complete the global description of the disease. Abstract: Introduction: Autosomal recessive osteopetrosis (ARO) is a rare genetic disorder that is also called "malignant osteopetrosis" because it typically manifests within the first few months after birth and later manifests severe complications (blindness, deafness, facial palsy, dental caries, hypocalcemia) and medullary haematopoetic disorders. The aim of this study is to describe lesions and conclude hypothetical clinical symptoms by performing a CT-scan analysis on an early 19th century human skull preserved in the Dupuytren museum collection (Paris). Materials and methods: The dried skull was examined and described using classical methods of paleopathology. We conducted additional research using historical data on the skull and a CT scan was performed. Results: Screening of the archives from the museum allowed us to estimate the skull's origin as somewhere between 1850 and 1900, with an estimated age of six years. Several ducts and foramens of the skull and the facial bones were obstructed as a result of this disease, clinically corresponding to diffuse neurological (and also vascular) deficits. This devastating pathology led to many symptoms stemming from brain tissue damage and cranial nerve deficits, leading to the inevitable death of this child. These symptoms include headache, intracranial hypertension with vomiting, blindness, exophthalmos, deafness, oral breathing, eating disorder (suffocation), facial palsy, balance disorder (excessive weight, vestibulo-cochlear and cerebellar involvement). Conclusion: The study of this specimen from the 19th century confirms that the six-year old patient suffered from malignant osteopetrosis. CT-scan allowed confirmation of the diagnosis, as well as a complete description of the disease, and highlight a possible associated anaemia.